An Analysis of Papuan Students’ Interest in Learning Moi Language using KMOIS Application (Indonesian Moi Dictionary) at Information Technology Education Major - Sahiruddin, Sahiruddin (INTERACTION: Jurnal Pendidikan Bahasa, 2022)
This study aims to determine the interest in learning the MOI language of information technology education students using the KMOIS application (Indonesian Dictionary Moi). This study uses a descriptive qualitative approach. Data collection was carried out using interview, observation and documentation techniques. Data analysis used the Miles and Huberman model, namely data reduction, data display and conclusion drawing. The results showed that the interest in learning the Moi language of information technology education students from Papua was influenced by the difficulty of getting books about the Moi language and students thought that learning the Moi language was very difficult, so using the KMOIS application (Indonesian Dictionary of Moi) was very helpful in increasing students' interest in learning from Papua in learning the Moi language